The use of mixed methods in social research on gender issues: the case of violence and harassment in the world of work - Kazani, Aggeliki; Moschovakou, Nafsika (The Greek Review of Social Research, 2026)
The use of mixed methods in social research on gender issues is becoming increasingly prevalent, as it allows for the combined utilization of the advantages of each method. This article examines and proposes the integration of quantitative and qualitative research for the study of gender issues, as an approach that enables a more comprehensive exploration of the dimensions of social phenomena and provides a reliable basis for gender policy development. As an example, primary research conducted on the field of violence and harassment in the workplace is presented to highlight the value and contribution of using mixed methods.